Analisis Kesenjangan ITSM Berbasis ITIL pada Aplikasi Pengelolaan Gedung - Cahyanto, Mahendra; Hartawan, Rumadi; Yulianto, Akmal Budi (STMIK Banjarbaru, 2026)
The development of information technology has encouraged the use of information systems in office building management. PT Binayasa Putrabatara has implemented a Building Management Information System (BMIS) to support building operation services. However, several issues are still encountered, such as delays in incident handling, lack of problem documentation, and the absence of structured change management procedures. This study aims to analyze the implementation of IT Service Management (ITSM) based on the Information Technology Infrastructure Library (ITIL) framework in the BMIS application and to identify gaps between the existing conditions and ITIL best practices. This research employs a qualitative descriptive method with a case study approach through interviews, observations, and documentation. The analysis focuses on Incident Management, Problem Management, and Change Management processes. The results indicate that ITSM implementation in BMIS has not fully complied with ITIL standards. Therefore, improvements are recommended, including enhanced service documentation, formal change procedures, and more structured service monitoring..Keywords: IT Service Management; ITIL; Gap Analysis; Building Management Information SystemAbstrakPerkembangan teknologi informasi mendorong pemanfaatan sistem informasi dalam pengelolaan gedung perkantoran. PT Binayasa Putrabatara telah menerapkan Building Management Information System (BMIS) untuk mendukung operasional pengelolaan gedung. Namun, dalam implementasinya masih ditemukan kendala seperti keterlambatan penanganan insiden, kurangnya dokumentasi permasalahan, serta belum optimalnya prosedur pengelolaan perubahan sistem. Penelitian ini bertujuan untuk menganalisis penerapan IT Service Management (ITSM) berbasis Information Technology Infrastructure Library (ITIL) pada aplikasi BMIS serta mengidentifikasi kesenjangan antara kondisi eksisting dan praktik terbaik ITIL. Metode yang digunakan adalah deskriptif kualitatif dengan pendekatan studi kasus melalui wawancara, observasi, dan dokumentasi. Analisis difokuskan pada proses Incident Management, Problem Management, dan Change Management. Hasil penelitian menunjukkan bahwa penerapan ITSM pada BMIS belum sepenuhnya sesuai dengan standar ITIL. Oleh karena itu, direkomendasikan perbaikan berupa peningkatan dokumentasi layanan, penerapan prosedur perubahan formal, serta monitoring layanan yang lebih terstruktur..